Spin dynamics of hydrothermally synthesized δ-MnO2nanowhiskers - Gangwar D.; Rath C. (My University, 2025)
We have reported novel 2D monoclinic, P63/mnm, δ-MnO2 nanowhiskers synthesized through a simple and facile hydrothermal route under optimized conditions without using any template. The X-ray diffraction pattern shows the formation of the δ phase of MnO2, which is further confirmed by Fourier transform infrared (FT-IR) spectroscopy and Raman spectroscopy. The transmission electron micrograph revealed nanowhiskers having a diameter of ∼7 nm and the high-resolution TEM and SAED patterns demonstrated the interplanar spacing and distinguished diffraction rings corresponding to the monoclinic phase of δ-MnO2. Fitting the temperature-dependent susceptibility with the Curie-Weiss law confirms the strong antiferromagnetic ordering and high effective magnetic moment of Mn4+ present in δ-MnO2. The large effective magnetic moment is attributed to the presence of both Mn3+ and Mn4+, as confirmed by XPS. The reduced valency of Mn from 4 to 3 is accompanied with oxygen vacancies, affording the exact composition of MnO1.58. The dynamic magnetic properties of the δ-MnO2 nanowhiskers were investigated using the frequency-dependent AC susceptibility fitted with various phenomenological models like the Vogel-Fulcher law and power law, indicating the existence of interacting spin clusters, which could freeze at ∼11.2 K. The time dependence of thermoremanent magnetization fitted well with a stretched exponential function, supporting the existence of relaxing spin clusters. Thus, the spin glass relaxation in the δ-MnO2 nanowhiskers is attributed to the interaction between Mn4+ and Mn3+, which results in intrinsic magnetic frustration and weak ferromagnetism with finite coercivity below Tf. This journal is © the Owner Societies.